2019
DOI: 10.1021/acs.energyfuels.9b02349
|View full text |Cite
|
Sign up to set email alerts
|

Green Fuel Desulfurization with β-Cyclodextrin Aqueous Solution for Thiophenic Sulfides by Molecular Inclusion

Abstract: Achieving green fuel desulfurization for thiophenic sulfides (TpSs) is a very urgent theme for the production of clean oil. Herein, an aqueous solution of β-cyclodextrin (βCD) as a novel desulfurization agent that is environmentally friendly and low cost was approached in the inclusion removal of the TpSs in fuel. It was found that βCD aqueous solution (βCD aq) has high selectivity to remove the TpSs in fuel. The desulfurization conditions of the molecular inclusion with βCD aq are significantly more moderate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…It was mainly due to the sulfur atom’s electron-withdrawing ability for hydrogen atoms, leading to the strong interaction between DES and DBT . In addition, the characterization signals at DBT (8.34, 8.01, and 7.50 ppm) were hardly recognized after the reaction due to the shielding effect of DES on DBT . As per the above analysis, there was an interaction between DES and the sulfur atom of DBT.…”
Section: Resultsmentioning
confidence: 81%
“…It was mainly due to the sulfur atom’s electron-withdrawing ability for hydrogen atoms, leading to the strong interaction between DES and DBT . In addition, the characterization signals at DBT (8.34, 8.01, and 7.50 ppm) were hardly recognized after the reaction due to the shielding effect of DES on DBT . As per the above analysis, there was an interaction between DES and the sulfur atom of DBT.…”
Section: Resultsmentioning
confidence: 81%
“…[16][17][18][19] The phenyl isocyanate on the CD ring can cause additional π-π interaction between the CD and analyte, which may contribute to the complexation of the CD cavity. [20][21][22][23][24][25] In addition, the introduction of an electron-withdrawing halogen element at the 3 or 4 positions of the phenyl isocyanate may have a positive effect on the π-π bond and comprehensively improve the recognition ability of the cyclodextrin chiral stationary phase column for chiral drugs. [26][27][28][29] The stationary phase supported on modified microspheres is an effective separation that has been proved.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, some cyclodextrins of chloro‐isonitriles can interact with chiral drugs, they show a wide range of adsorption selectivity 16–19 . The phenyl isocyanate on the CD ring can cause additional π–π interaction between the CD and analyte, which may contribute to the complexation of the CD cavity 20–25 . In addition, the introduction of an electron‐withdrawing halogen element at the 3 or 4 positions of the phenyl isocyanate may have a positive effect on the π–π bond and comprehensively improve the recognition ability of the cyclodextrin chiral stationary phase column for chiral drugs 26–29 .…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that the cylindrical structure of β ‐CD was used as a host‐guest system to load pharmaceutical materials. [ 32–35 ]…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that the cylindrical structure of β-CD was used as a host-guest system to load pharmaceutical materials. [32][33][34][35] Various drugs have been utilized with different carriers for drug delivery purposes. [36] Herbal medicines extracted from natural resources are of particular importance in medical science due to their low side effects.…”
Section: Introductionmentioning
confidence: 99%